2014
DOI: 10.1089/brain.2014.0274
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia Is Associated with Decreased Connectivity Between Pain- and Sensorimotor Brain Areas

Abstract: Fibromyalgia (FM) is a syndrome characterized by chronic pain without known peripheral causes. Previously, we have reported dysfunctional pain inhibitory mechanisms for FM patients during pain administration. In this study we employed a seed correlation analysis, independent component analysis (ICA), and an analysis of fractional amplitude of low frequency fluctuations (fALFF) to study differences between a cohort of female FM patients and an age-and sex-matched healthy control group during a resting-state con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 38 publications
7
98
0
1
Order By: Relevance
“…The elements of this network may be engaged in emotional processing, executive and cognitive functions [54][55][56], and pain perception [57,58]. Previous resting state fMRI studies have demonstrated aberrant DMN connectivity in patients with fibromyalgia [59][60][61][62]. Moreover, Napadow and colleagues have provided preliminary evidence that intrinsic DMN connectivity can be used as an objective marker in fibromyalgia for tracking intra-subject changes in spontaneous chronic pain [60].…”
Section: The Mpfc Pcc and Parahippocampal Gyrusmentioning
confidence: 99%
“…The elements of this network may be engaged in emotional processing, executive and cognitive functions [54][55][56], and pain perception [57,58]. Previous resting state fMRI studies have demonstrated aberrant DMN connectivity in patients with fibromyalgia [59][60][61][62]. Moreover, Napadow and colleagues have provided preliminary evidence that intrinsic DMN connectivity can be used as an objective marker in fibromyalgia for tracking intra-subject changes in spontaneous chronic pain [60].…”
Section: The Mpfc Pcc and Parahippocampal Gyrusmentioning
confidence: 99%
“…A number of studies have provided further evidence of dysfunctional connectivity of the pain network in FMS (Jensen et al, 2012;Flodin et al, 2014). One study found that FMS patients exhibited higher sensitivity to pain provocation than controls and that they required less pressure to evoke equal pain, but they failed to respond to pain provocation in the primary link in the descending pain-regulating system (the rostral anterior cingulate cortex) (Flodin et al, 2014).…”
Section: Pathogenesismentioning
confidence: 99%
“…One study found that FMS patients exhibited higher sensitivity to pain provocation than controls and that they required less pressure to evoke equal pain, but they failed to respond to pain provocation in the primary link in the descending pain-regulating system (the rostral anterior cingulate cortex) (Flodin et al, 2014). Another study comparing the functional connectivity of the descending pain inhibitory network in age-matched FMS patients and healthy controls found that patients displayed less connectivity within the brain's pain inhibitory network during calibrated pressure pain compared with healthy controls (Jensen et al, 2012).…”
Section: Pathogenesismentioning
confidence: 99%
“…Consequently muscle weakness can be linked to peripheral and central mechanisms [23]. Several studies found no correlation in muscle histopathologically and muscle metabolism in FMS etiopathogenesis [24,25].…”
Section: Citation: Harman H öNeş K Ayna Ab (2015) the Effects Of Hamentioning
confidence: 99%